Effects of different extracted components from petroleum pitch on mesophase development. (15th June 2018) - Li, Ming; Liu, Dong; Men, Zhuowu; Lou, Bin; Yu, Shitao; Ding, Junwei; Cui, Wenlong
Graphical abstract: Highlights: Effects of extracted components on mesophase development were investigated. Interactive effect indexes were cited to study the cooperation of components. Orderliness of microcrystal structure depended on the alkyl structure in feedstock. Naphthene had better effects on the formation of mesophase pitch than alkyl chain. Abstract: Naphthenic-based petroleum pitch was divided into three components, including heptane-soluble (HS), heptane-insoluble/toluene-soluble (HITS) and toluene-insoluble (TI), by sequential extraction with heptane and toluene. Mesophase pitches were prepared by direct condensation of the extracted components and their mixtures. Effects of different components on formation and development of mesophase structures were investigated. Results showed that HITS was the optimal component for preparation of mesophase pitch with large domain structure, low softening point, high carbon residue and ordered microcrystal structure. Interactive effect indexes were cited to monitor the interaction of these components on mesophase development. The component HS with rich alkyl chains accelerated the carbonization via chain breaking at the initial stage of reaction, and HITS with abundant naphthenic structures alleviated the carbonization through hydrogen-transfer reaction during the aggregation process of aromatic molecules, and TI as initial nucleus could trigger the generation of mesophase spheres. However, the mixture of HS and TI possessed a weaker interactive effect on mesophase development compared to the other two mixtures. This was mainly due to the differences in molecular weight distribution and molecular structure between HS and TI. Furthermore, naphthenic structures had a better improving effect than alkyl chains on the generation of high-quality mesophase pitches.